Analisis Yuridis Tingkat Kepatuhan Membayar Pajak Masyarakat Indonesia - Gerald Samuel (Fakultas Hukum Universitas Mulawarman, 2022)
The development of a country is determined by the community and the government that regulates it. If the government makes good laws and regulations, the community will always comply with these regulations. Taxes are things that are regulated in laws and regulations. In this case, taxes are an obligation for the community to pay them. The type of research in the legal article entitled Juridical Analysis of the Compliance Level of Paying Taxes for the Indonesian Society is doctrinal or normative legal research. Taxes themselves have essential benefits for the development of the Indonesian state because taxes are a source of state treasury income which is ultimately used for public welfare. This study aims to determine the benefits of taxes, government efforts, and the influence of the Indonesian people's understanding of the importance of paying taxes to create public welfare in Indonesia. Keywords: tax; taxpayer; tax benefits; awareness of paying taxes; tax compliance